Development of a promising system for diagnosing the frogs of railroad switches using the transverse profile measurement method - Kovalchuk, Vitalii; Sysyn, Mykola; Hnativ, Yuriy; Bal, Olena; Parneta, Bogdan; Pentsak, Andriy (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed a system for diagnosing the frogs of railroad switches, based on the application of modern microcontrollers of the type ESP with high technical characteristics and the simultaneous use of the information technology IoT (Internet of Things). The proposed system has advantages over mechanical systems in terms of the accuracy of data, their operational processing and submission to user in order to analyze technical condition of frogs at railroad switches. The results of measuring the transverse profile of frogs at railroad switches make it possible to take scientifically-substantiated decisions regarding the need for recovery repair of frogs by the method of surfacing and for control over gradual decrease in their carrying capacity, for establishing their actual technical condition and residual resource. We carried out experimental-theoretical research into longitudinal profile of frogs at railroad switches laid on the reinforced concrete bars. It was established as a result that after passing 50–65 million tons of cargo (that corresponds to the medium degree of wear) the trajectory takes the shape of a bump. We observe sharp hollows on the reinforced concrete base in the zone where a wheel rolls from a rail wing onto the core, characterized by significant total inclination. Subsequently, when the passed cargo increases, the number of sinusoidal irregularities grows. At wear close to maximal (80–95 million tons passed), the percentage of unfavorable trajectories (sinusoidal and hollows) grows; at low wear, they make up 49.8 %, at a wear of 5–6 mm and larger – 88.3 %. Sometimes there is a transformation of the sinusoidal irregularities into the wave-shaped ones. We have established characteristic motion trajectories of the center of mass of the wheel over the frog depending on the wear of rail wings and the core of a frog and the passed cargo. A mathematical model was constructed for predicting the wear of frog profile depending on the total weight of passed cargo.